XALQARO SAVDONING TO‘LOV BALANSI VA VALYUTA KURSLARIGA TA’SIRINI O‘RGANISH (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This article examines the impact of international trade on the balance of payments and exchange rates. The article analyzes international trade transactions, the formation of the balance of payments, the impact of exchange rates on the economy and trade volume. It also graphically illustrates the relationship between re-exports and real exchange rates, highlighting the role of exchange rates in economic stability and global trade.